Affirmative action in Malaysia (1971-1990) in the light of maqasid al-shari'ah - Mohd Effuan Aswadi bin Abdul Wahab (International Institute of Islamic Civilisation and Malay World (ISTAC), International Islamic University Malaysia, 2018)
This study analyses affirmative action policies and programmes from the early 1970s to the end of the 1990s in Malaysia through the New Economic Policy (NEP) in light of Maqasid al-Shari'ah, namely daruriyat (essential), hajiyat (exigencies) and tahsiniyat (enhancement) and also from the perspective of Maqasid based ijtihad. The objectives of NEP are to increase the income level and employment across all sectors in society and to reduce and eliminate identification of race in certain industries in the economy. These policies are examined especially in the occupational sector and educational system where ethnic quota was practised and subsidies were granted to small and medium enterprises (SMEs) owned by the Malays and the Bumiputra. Five criteria of the daruriyat, namely, the protection of faith (al-Din), the protection of self (an-nafs), the protection of intellect (al-Aql), the protection of posterity (an-nasl) and the protection of wealth (al-Mal) are considered on whether affirmative action programmes fulfilled the criteria. Aspects from hajiyat and tahsiniyat were also looked into. Since affirmative action is a new phenomenon and there is no direct ruling from Al Qur'an and the Sunnah, then Maqasid based ijtihad are used. Imam al-Shatibi categorizes the Maqasid based ijtihad into four: there must be inseparability of texts and rulings from their intents, it needs to combine universal principles with evidence applicable to a particular case, the goals must be to achieve benefit and prevent harm and lastly the consideration of the outcomes. This study uses qualitative content analysis. It was found that affirmative action policies in Malaysia during the period of 1970s until the 1990s did not contradict Maqasid al-Shari'ah principle although there are no clear practices of it during the early Islamic period. There are advantages and disadvantages of practising these policies. Based on the results gained, it clearly shows that the advantages outweighed disadvantages. The affirmative action policies have been introduced to promote peace and equal distribution of wealth in this multi ethnic society in Malaysia. The thesis also calls for Islamic scholars to look at modern economic challenges in this era of nation state and to explore Maqasid based ijtihad further for the benefit of the ummah and the civilizational of Islam.